The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1590/s0100-879x2001000600020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-arginine on the diaphragm muscle twitches elicited at different frequencies of nerve stimulation

Abstract: In rats, the nitric oxide (NO)-synthase pathway is present in skeletal muscle, vascular smooth muscle, and motor nerve terminals. Effects of NO were previously studied in rat neuromuscular preparations receiving low (0.2 Hz) or high (200 Hz) frequencies of stimulation. The latter frequency has always induced tetanic fade. However, in these previous studies we did not determine whether NO facilitates or impairs the neuromuscular transmission in preparations indirectly stimulated at frequencies which facilitate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Moreover, Wang et al in 1995 noticed that c.GMP-dependent kinase phosphorylate the nicotinic acetylcholine receptor subunits in cultured myocytes. 16,17,18 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, Wang et al in 1995 noticed that c.GMP-dependent kinase phosphorylate the nicotinic acetylcholine receptor subunits in cultured myocytes. 16,17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Queiroz and Alves -Do-Prado 2001 suggested that, the increase in the amplitude of muscle contraction produced at different frequencies, depend on the metabolism of L-argnine producing additional NO in the tissues and its ability to scavenge superoxide anions. They reported that NOS activity might change according to the applied frequency of stimulation to the motor nerve 3 . It was also possible that during high-frequency stimulation, presynaptic as well as postsynaptic components are activated through a variety of signal transduction cascades.…”
Section: The Effect Of Nitric Oxide On the Rat Diaphragm At Differentmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, L-arginine and SIN-1 reduce the maximal tetanic tension (postsynaptic action) when a high stimulation frequency is applied directly to diaphragm preparations previously treated with d-tubocurarine (11). The presynaptic and postsynaptic effects of NO were also observed in assays performed at high frequency with superoxide dismutase, a selective scavenger of superoxide anion radicals (11,12). Since the NO-induced neuromuscular effects may depend on a direct and/or indirect interaction with K + channels, the present study was undertaken to determine the neuromuscular effects of the NO precursor L-arginine and of 8-Br-cGMP on the rat phrenic nerve diaphragm preparation previously treated with a K + channel blocker.…”
Section: -Aminopyridine Inhibits the Neuromuscular Effects Of Nitricmentioning
confidence: 99%